Designing a terahertz optical sensor based on helically twisted photonic crystal fiber for toxic gas sensing - Vahid Sharif; Hana Saberi; Hassan Pakarzadeh (Scientific Reports)
Abstract A novel helically twisted photonic crystal fiber (PCF) is designed and proposed for sensing toxic gases with refractive indices ranging from 1.00 to 1.08. The PCF consists of twelve hollow pipes arranged circularly around the hollow core to support THz radiation propagation. Low-loss polymer Topas is used as the background material of cladding. The fiber is twisted 360° over 50 cm to enhance anti-resonance in the THz region. The fundamental LP01 mode is analyzed using the finite-difference eigenmode (FDE) method. The sensor operates across four frequency bands (0.2 to 3.0 THz) with minimal transmission loss (~ 10⁻⁴ 1/cm). Key parameters such as refractive index sensitivity, relative sensitivity, resolution, and figure of merit (FOM) are evaluated. The average refractive index sensitivities are 1450, 2250, 3000, and 2550 for Bands 1 to 4, respectively, with 100% relative sensitivity across all bands. The sensor detects refractive index changes as small as 10⁻⁴. The FOM, defined as the inverse of the full width at half maximum, exceeds 30 1/RIU, reaching up to 250 1/RIU due to sharp resonance peaks. Compared to other THz sensors, this design offers enhanced performance in sensing gases like SOx, NOx, and CO, while maintaining a simple structure.